The Language Of Silence In The Therapeutic Setting Of Dental Medicine - Dias, Maria do Rosário; Naben, Letícia; Ferreira, Ana; Mendes, José João (Advances in Social Sciences Research Journal, 2019)
The aim of the present study is to explore the perceptions associated with the non-verbal communication that is installed in the therapeutic setting of the practice of Dental Medicine, namely to: a) Determine the extent to which non-verbal signals are apprehended both by Dentists and Patients; b) Evaluate the perceptions of Dentists and Patients when exposed to the same non-verbal stimuli; C) Verify the existence of significant differences between Dentists and Patients in the capacity of apprehension of the signs. The results suggest that Patients do not seem to be aware of how they communicate their discomfort through non-verbal language. However, Dentists are aware that their adoption of a discomforting facial expression can condition the Patient's emotional state. Deepening the knowledge of non-verbal communication (NVC) allows Dentists to develop their communication skills, thus increasing the choice of the most appropriate intervention strategies in Dental Medicine Health Care.